The Influence of Generative-Based Online Training Models on the Digital Capabilities of Businesses - Mafrur Udhif Nofaizzi; Dedi Kuswandi (Yayasan Adra Karima Hubbi, 2024)
This research aims to test the effect of a generative-based online training model on the digital capabilities of MSME players. This research uses quantitative research methods where there are two groups, namely experimental and control, with 20 participants each. Before and after being given treatment, participants were tested using a 25-question multiple choice test. The analysis test uses the normality test and the paired sample t test. The results showed significance for both the experimental group and the control group with a score of <0.05. This shows that there is a positive influence between the generative-based online training model and increasing digital capabilities for MSME players